DEVELOPMENT OF DIGITALIZATION OF EARLY CHILDREN LEARNING AT TK AL-HIDAYAH 25 AJUNG JEMBER - Ela Windi Safitri; Yasuli Bindulem; Nurul Anam; Ratri Kurnia Pratiwi (FORPIM PTKIS ZONA TAPAL KUDA, 2023)
Modern learning is marked by the delivery of material using digital media. Digital media is an important learning component in early childhood education institutions. Therefore, this study aims to determine the development of digitalization of early childhood learning on the